2014
DOI: 10.1007/s40265-014-0247-z
|View full text |Cite
|
Sign up to set email alerts
|

Sofosbuvir: A Review of its Use in Patients with Chronic Hepatitis C

Abstract: Sofosbuvir (Sovaldi(®)) is a nucleotide hepatitis C virus (HCV) NS5B polymerase inhibitor that has pangenotypic antiviral activity and a high genetic barrier to resistance. This article reviews the clinical efficacy and tolerability of sofosbuvir in patients with chronic hepatitis C and summarizes its pharmacological properties. Interferon-free treatment with sofosbuvir plus ribavirin achieved high sustained virological response (SVR) rates in treatment-naïve and treatment-experienced patients with HCV genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 39 publications
(183 reference statements)
1
58
0
Order By: Relevance
“…Studies investigating the pharmacokinetics of single‐ or multi‐dosing reported that no dosage modifications were required for patients with mild‐to‐moderate renal impairment. However, for patients with creatinine clearance less than 30 mL/min including those on haemodialysis, no dosage recommendation for sofosbuvir has been established . Single‐dose pharmacokinetics demonstrated the area under the curve (AUC) of the sofosbuvir metabolite GS‐331007 and, to a lesser extent, sofosbuvir itself, increased with worsening renal status.…”
Section: Adverse Events Of Daa Combination Therapiesmentioning
confidence: 99%
“…Studies investigating the pharmacokinetics of single‐ or multi‐dosing reported that no dosage modifications were required for patients with mild‐to‐moderate renal impairment. However, for patients with creatinine clearance less than 30 mL/min including those on haemodialysis, no dosage recommendation for sofosbuvir has been established . Single‐dose pharmacokinetics demonstrated the area under the curve (AUC) of the sofosbuvir metabolite GS‐331007 and, to a lesser extent, sofosbuvir itself, increased with worsening renal status.…”
Section: Adverse Events Of Daa Combination Therapiesmentioning
confidence: 99%
“…It is important to note that the risk of the development of DDIs differs between the different new HCV direct acting antivirals. The NS5B polymerase inhibitor, sofosbuvir, is expected to cause fewer DDIs However, the second wave PI, simeprevir, is an inhibitor and substrate of CYP3A4. The NS5A inhibitor, daclatasvir, is a substrate of CYP3A4 and a substrate and inhibitor of P‐glycoprotein .…”
Section: Discussionmentioning
confidence: 99%
“…Oral sofosbuvir was generally well tolerated in CHC patients [97] ; (7) In combinations with other oral DAAs, ombitasvir (an inhibitor of the HCV NS5A) achieves very high rates of SVR (about 95%) in patients with HCV genotype 1 infection with a good tolerability [98] ; and (8) Combination of daclatasvir and asunaprevir results in a very high rate of viral eradication in both treatment-naïve and treatment-experienced patients, with a SVR rate of 80%-90% [99] . In October of 2014, FDA approved…”
Section: Treatmentmentioning
confidence: 97%